Application of mineral filler in surface layer of three-layer particle board and its effect on material properties as a function of filler content. (2nd July 2020) - Ozyhar, Tomasz
ABSTRACT: Addition of mineral filler in the surface layer of three-layer particle board and its influence on material properties was studied as a function of filler content. Three-layer particle board with a density of 700 kg m −3 and 0, 10, 20, and 40% weight fraction (wt-%) of calcium carbonate filler in surface layers was produced in laboratory scale using urea formaldehyde as resin. The effect of inorganic filler on elastic and strength properties, dimensional stability and formaldehyde emissions was investigated. The results demonstrated that the addition of filler in amounts up to 10 wt-% in surface layers does not significantly affect mechanical properties. Further increase in filler addition above 10 wt-% resulted in a nearly linear decrease in bending properties and increase in water uptake, however did not significantly affect dimensional stability and formaldehyde emissions.